Brachial-ankle pulse wave velocity is associated with coronary calcification among 1131 healthy middle-aged men. (15th June 2015) - Vishnu, Abhishek; Choo, Jina; Wilcox, Bradley; Hisamatsu, Takashi; Barinas-Mitchell, Emma J.M.; Fujiyoshi, Akira; Mackey, Rachel H.; Kadota, Aya; Ahuja, Vasudha; Kadowaki, Takashi; Edmundowicz, Daniel; Miura, Katsuyuki; et al.
Abstract: Background: Brachial-ankle pulse wave velocity ( ba PWV) is a simple and reproducible measure of arterial stiffness and is extensively used to assess cardiovascular disease (CVD) risk in eastern Asia. We examined whether ba PWV is associated with coronary atherosclerosis in an international study of healthy middle-aged men. Methods: A population-based sample of 1131 men aged 40–49 years was recruited — 257 Whites and 75 Blacks in Pittsburgh, US, 228 Japanese-Americans in Honolulu, US, 292 Japanese in Otsu, Japan, and 279 Koreans in Ansan, Korea. ba PWV was measured with an automated waveform analyzer (VP2000, Omron) and atherosclerosis was examined as coronary artery calcification (CAC) by computed-tomography (GE-Imatron EBT scanner). Association of the presence of CAC (defined as ≥ 10 Agatston unit) was examined with continuous measure as well as with increasing quartiles of ba PWV. Results: As compared to the lowest quartile of ba PWV, the multivariable-adjusted odds ratio (95% Confidence Interval [CI]) for the presence of CAC in the combined sample was 1.70 (0.98, 2.94) for 2nd quartile, 1.88 (1.08, 3.28) for 3rd quartile, and 2.16 (1.19, 3.94) for 4th quartile (p-trend = 0.01). The odds for CAC increased by 19% per 100 cm/s increase (p < 0.01), or by 36% per standard-deviation increase (p < 0.01) in ba PWV. Similar effect-sizes were observed in individual races, and were significant among Whites, Blacks and Koreans. Conclusion: ba PWV is cross-sectionally associated with CAC among healthy middle-aged men. The association was significant in Whites and Blacks in the US, and among Koreans. Longitudinal studies are needed to determine its CVD predictive ability.